2016
DOI: 10.1016/j.marpol.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the health benefits of physical activities in the marine environment and their importance for marine spatial planning

Abstract: The marine environment provides a number of services which contribute to human wellbeing including the provision of food, regulation of climate and the provision of settings for cultural gains. To ensure these services continue to be provided, effective management is required and is being strategically implemented through the development of marine spatial plans. These plans require an understanding of the costs and benefits associated with alternative marine uses and how they contribute to human well-being. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Following this evaluation approach and assuming a value of £20,000 per QALY, White et al (2016) evaluate that the QALYs gained through physical exercise carried out in natural environments in England may be worth over £2bn a year. Along the same lines, Papathanasopoulou et al (2016) suggest that increasing marine physical activity in the UK is worth between £176m and £746m a year.…”
Section: Increased Exercisementioning
confidence: 89%
“…Following this evaluation approach and assuming a value of £20,000 per QALY, White et al (2016) evaluate that the QALYs gained through physical exercise carried out in natural environments in England may be worth over £2bn a year. Along the same lines, Papathanasopoulou et al (2016) suggest that increasing marine physical activity in the UK is worth between £176m and £746m a year.…”
Section: Increased Exercisementioning
confidence: 89%
“…For example, including the healthcare savings and societal benefits of physical activities in impact assessments alongside the need for local economic growth in the marine environment, could influence marine spatial planning in terms of improving coastal access and water quality. A recent study, (Papathanasopoulou et al, 2016) estimated the monetary and non-monetary contribution of physical activities to quality adjusted life years (QALYs) in the UK. They found that physical activities undertaken in aquatic environments provide a total gain of 24,853 QALYs nationally, worth ca.…”
Section: Marine Activity Time Period Doi(€)mentioning
confidence: 99%
“…On the one hand, these places are seen as particularly relaxing and good for reducing stress and inducing positive emotions (Cocker, 2012;MacKerron & Mourato, 2013;White, Pahl, Ashbullby, Herbert, & Depledge, 2013). On the other hand, for many they also offer the opportunity to engage in, potentially strenuous, physical activities such as kayaking, sailing, open water swimming and, of particular interest for the current research, stand up board-riding or 'surfing' (Papathanasopoulou et al, 2016;White, Pahl, Wheeler, Fleming, & Depledge, 2016;White, Wheeler, Herbert, Alcock, & Depledge, 2014).…”
Section: Engaging With the Marine Environment And Surfingmentioning
confidence: 99%